Presentation and outcomes of patients with thoracic and lumbosacral spinal epidural arteriovenous fistulas: a systematic review and meta-analysis. (30th August 2018) - Byun, Jun-Soo; Tsang, Anderson Chun On; Hilditch, Christopher Alan; Nicholson, Patrick; Fang, Yi-Bin; Krings, Timo; Pereira, Vitor Mendes; Lanzino, Giuseppe; Brinjikji, Waleed
Abstract : Background and purpose: Thoracolumbar and sacral spinal epidural arteriovenous fistulas (SEDAVFs) are an increasingly recognized form of spinal vascular malformation. The purpose of this study was to perform a systematic review of the demographics, clinical presentation and treatment results of thoracolumbar SEDAVFs. Materials and methods: Pubmed, Scopus and Web of Science databases were searched from January 2000 to January 2018 for articles on treatment of SEDAVFs. Pooled data of individual patients were analyzed for demographic and clinical features of SEDAVFs as well as treatment outcomes. Results: There were 125 patients from 11 studies included. Mean age was 63.5 years. There was a male sex predilection (69.6%). Sensory symptoms including pain or numbness were the most frequently presenting symptoms. Fistula location was the lumbosacral spine in 79.2% and the thoracic spine in 20.8%. Involvement of intradural venous drainage was more common than extradural venous drainage only (89.6% vs 10.4%). Of the 123 treated patients, endovascular therapy was performed in 67.5% of patients, microsurgery in 23.6%, and combined treatment in 8.9%. The overall complete obliteration rate was 83.5% and did not differ between groups. Clinical symptoms improved in 70.7% of patients, were stable in 25%, and worsened in 1.7% with no difference between treatment modalities. Conclusions: Thoracic and lumbosacral SEDAVFs often present with symptoms secondary to congestive myelopathy or compressive symptoms. Both endovascular and microsurgical treatments were associated with high obliteration rates and good clinical outcomes.